The Prospect of New Provincial Renewable Portfolio Standard in China Based on Structural Data Analysis - Bu, Yinhe; Zhang, Xingping (Frontiers in Energy Research, 2020)
The new renewable portfolio standard policy issued by China on May 2019 stipulates a specific promotion scheme of a quota obligation mainly on power supply companies and power consumers to sell or buy an increasing proportion of their electricity from renewable energy sources. The quota is essentially switched from the supply side to the demand side and will be provincially distributed and assessed, consequently motivating the provincial power system to accommodate a more renewable energy power. This paper proposes a prospect analysis by assessing the completion pressure of a newly modified quota in 30 provinces across Mainland China. The results show that 17 provinces enjoy the challenging completion pressure, while 10 provinces make it relatively easy to complete. Structural data analysis toward the provincial power supply structure and electricity balance is then put forward and reveals unfavorable factors for activating completion potential. Systematical measures are correspondingly introduced from the supply side, grid side, and demand side of the power system, with accompanying policy implications toward the core position of the power grid corporation and coordinated market-based mechanism simultaneously proposed.